Visualization of Viral Infection Dynamics in a Unicellular Eukaryote and Quantification of Viral Production Using Virus Fluorescence in situ Hybridization - Castillo, Yaiza M.; Sebastián, Marta; Forn, Irene; Grimsley, Nigel; Yau, Sheree; Moraru, Cristina; Vaqué, Dolors (Frontiers in Microbiology, 2020)
One of the major challenges in viral ecology is to assess the impact of viruses in controlling the abundance of specific hosts in the environment. To this end, techniques that enable the detection and quantification of virus–host interactions at the single-cell level are essential. With this goal in mind, we implemented VirusFISH (Virus Fluorescence in situ Hybridization) using as a model the marine picoeukaryote Ostreococcus tauri and its virus OtV5. VirusFISH allowed the visualization and quantification of the fraction of infected cells during an infection cycle in experimental conditions. We were also able to quantify the abundance of free viruses released during cell lysis and give an estimation of the burst size in a non-axenic culture, since we could discriminate OtV5 from phages. Our results showed that although the major lysis of the culture occurred between 24 and 48 h after OtV5 inoculation some new viruses were already produced between 8 and 24 h, propagating the infection. The estimation of the burst size for the O. tauri–OtV5 system was 7±0.4 OtV5 per cell, in the low end of the range obtained in previous studies. With this work we demonstrate that VirusFISH is a promising technique to study specific virus–host interactions in non-axenic cultures, and set the ground for its application in complex natural communities.